Integracja na styku kultur. Islamsko-chrześcijańskie pogranicze Bośni i Hercegowiny - Pilarska, Justyna (Zakład Pedagogiki Społecznej Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
Muslim communities in the Balkans, in which the practice of Islam developed in the European context, can be used as an exemplification of the bridge between the Islamic East and the Christian West. Although for over 400 years Bosnia was under the Ottoman rule, Muslims became one of the many communities contributing to the dynamic area of ontological and axiological negotiations within the cultural borderland, sharing the living space with members of the Orthodox church, Catholics, and a small Jewish community. The history of the Muslim-Christian contacts in Bosnia includes the examples of collisions as well as encounters initiated both by Christians and Muslims. This article analyses the religious borderland in the historical and contemporary cultural and social context of Bosnia-Herzegovina, revealing its specificity, dynamics and (often unsuccessful) attempts to conceptualize it from the perspective of the Eurocentric discourse.
Keywords: cultural borderland; Bosnian Islam; inter-religious dialogue; Bosnia-Herzegovina